2017
DOI: 10.1051/parasite/2017018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of astaxanthin in mice acutely infected withTrypanosoma cruzi

Abstract: During Trypanosoma cruzi infection, oxidative stress is considered a contributing factor for dilated cardiomyopathy development. In this study, the effects of astaxanthin (ASTX) were evaluated as an alternative drug treatment for Chagas disease in a mouse model during the acute infection phase, given its anti-inflammatory, immunomodulating, and anti-oxidative properties. ASTX was tested in vitro in parasites grown axenically and in co-culture with Vero cells. In vivo tests were performed in BALB/c mice (4–6 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…[92]. In another study, the parasitic (Trypanosoma cruzi) load was significantly reduced in vitro, but no significant observation was observed in vivo when studied in a mouse model [93]. In another study, AXT showed a potential antibacterial effect in a Helicobacter pylori-infected mouse model.…”
Section: Biological Activity Of Carotenoidsmentioning
confidence: 96%
See 1 more Smart Citation
“…[92]. In another study, the parasitic (Trypanosoma cruzi) load was significantly reduced in vitro, but no significant observation was observed in vivo when studied in a mouse model [93]. In another study, AXT showed a potential antibacterial effect in a Helicobacter pylori-infected mouse model.…”
Section: Biological Activity Of Carotenoidsmentioning
confidence: 96%
“…Shanmugapriya et al formulated AXT-loaded nanoemulsions for treating infections caused by both Gram-positive and Gram-negative bacterial species[92]. In another study, the parasitic (Trypanosoma cruzi) load was significantly reduced in vitro, but no significant observation was observed in vivo when studied in a mouse model[93]. In another study, AXT showed a potential antibacterial effect in a Helicobacter pylori-infected mouse model.…”
mentioning
confidence: 99%
“…In the in vitro study of Trypanosoma cruzi, the viability of the parasite was decreased in doses of AST 200-300 µg/mL. Simultaneously, the authors did not observe the therapeutic effect of AST against acute T. cruzi infection in the mice model [35]. In animal studies of mice infected with Helicobacter pylori, it was shown that AST has an impact on the decrease of bacterial abundance in the stomach.…”
Section: Astaxanthinmentioning
confidence: 98%
“…The number of parasites used for challenge infection was variable, ranging from 1 × 10 1 to 1 × 10 5 blood trypomastigotes, that was mostly related to virulence of the parasite isolates but unrelated to the development of the acute or chronic phase. The antioxidant compounds used in these studies included phenyl-α-tert-butyl nitrone (PBN) [50,51], carvedilol, vitamin E (vitE) and/or vitamin C (vitC) [52,53], melatonin [54], curcumin [55], resveratrol, and astaxanthin [56]. Vitamin C was the most commonly used antioxidant, evalu-ated in five of the published studies.…”
Section: Antioxidant Effects In Experimental Models Of Chagas Diseasementioning
confidence: 99%
“…Three of the antioxidant compounds, vitC, curcumin, and PBN, were also evaluated in combination with benznidazole. Only astaxanthin was evaluated in combination with nifurtimox [56] ( Table 1). The oral route of administration of the antioxidant compounds was used in >80% the studies.…”
Section: Antioxidant Effects In Experimental Models Of Chagas Diseasementioning
confidence: 99%